Correlation between effective charge density and crosslinking efficiency of dicarboxylic acid containing highly anionic networks. (24th January 2023) - Ciftbudak, Sena; Orakdogen, Nermin
Abstract: By investigating the relationship between the swelling and deformation properties, an attempt was made to establish a correlation between microstructure and charge density of anionic polyacrylamide/itaconic acid (PAAm/ITA) hydrogels. The effective charge density of network dominated the microstructure of PAAm/ITA hydrogels. The porosity of anionic hydrogels increased with addition of diprotic ITA, and resulting microstructure determined the swollen state deformation. Based on effective charge density, the swelling gradually increased and maximum swelling was achieved with 14% ITA, while there was a 24-fold increase in gel volume relative to homopolymer network. The relationship between elasticity and crosslinking density was explained using Rubber elasticity theory on deformation behavior. A variety of factors that affect swelling and elasticity was explored such as effective charge density, crosslink density of anionic network as well as pH of solution and surfactant type. The equilibrium volume swelling ratio in water scales with network charge density by the relation φ V ∝ f eff 1.17, while the dependence of reduced modulus with equilibrium gel volume was found to be G r ≈ ( φ V ) − 0.28 indicating that equilibrium swollen PAAm/ITA hydrogels are in Gaussian regime. An empirical relationship has been found implying that by varying amount of ITA, the crosslinked structure and crosslinking density can be effectively controlled. PAAm/ITA hydrogels showed good reversible characteristics during repeated oscillations between pH 11.2 and 2.1, which is important for controlled drug delivery system. Rapid water penetration of PAAm/ITA hydrogels with internal morphology and high swelling resulting from the presence of ITA revealed internal adsorption sites for methyl violet and methylene blue. The adsorption kinetics followed a pseudo-second order and showed a two-stage intra-particle diffusion model. The results will contribute to the determination of correlation between anionic structure and properties for efficient and economical design of anionic materials for specific uses and industrial scale-up. Graphical abstract: Image 1 Highlights: A simple and efficient design of dicarboxylic acid containing highly anionic networks. On-off switching swelling according to degree of protonation of carboxyl moieties. Associative interactions between anionic network-surfactant species. Correlation between effective charge density and crosslinking efficiency. Flory-Rehner and Rubber-elasticity was combined to determine physico-mechnical properties.